2018
DOI: 10.1097/mco.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Hyperammonemia and proteostasis in cirrhosis

Abstract: Signaling via myostatin and eIF2α phosphorylation causes decreases in protein synthesis and mTORC1 activity with a parallel mitochondrial dysfunction and increased autophagy contributing to proteostasis perturbations during skeletal muscle hyperammonemia of liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 40 publications
1
67
0
Order By: Relevance
“…In skeletal muscle, impairment of mTORC1 signaling during hyperammonemia can occur as consequence of: (a) elevated levels of myostatin; (b) increased phosphorylation and activation of either the amino acid deficiency sensor general control non‐depressible 2 kinase (GCN2) or the eukaryotic initiation factor 2 alpha (eIF2α), an essential factor for protein synthesis; and (c) an impaired production of energy with excessive cataplerosis of α‐KG.…”
Section: Ammonia and Autophagymentioning
confidence: 99%
“…In skeletal muscle, impairment of mTORC1 signaling during hyperammonemia can occur as consequence of: (a) elevated levels of myostatin; (b) increased phosphorylation and activation of either the amino acid deficiency sensor general control non‐depressible 2 kinase (GCN2) or the eukaryotic initiation factor 2 alpha (eIF2α), an essential factor for protein synthesis; and (c) an impaired production of energy with excessive cataplerosis of α‐KG.…”
Section: Ammonia and Autophagymentioning
confidence: 99%
“…The effects and underlying mechanism of ammonia-induced fatigue remain controversial, especially with regard to peripheral effects. Recent studies in cirrhosis patients have revealed that hyperammonaemia impairs protein synthesis and induces mitochondrial dysfunction in skeletal muscle [11][12][13] . However, whether hyperammonaemia disturbs whole-body energy metabolism has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that ammonia activates phosphofructokinase and inhibits the oxidation of pyruvate to acetyl coenzyme A, which hinders the supply of adenosine triphosphate to skeletal muscle 5 . In addition, studies in cirrhosis patients have revealed that hyperammonaemia impairs protein synthesis and increases autophagy 11,12 , induces mitochondrial dysfunction due to cataplerosis of α-ketoglutarate, and lowers adenosine triphosphate content in muscle cells, which may contribute to skeletal muscle fatigue 12,13 . Since plasma concentrations of ammonia during exercise often reach or exceed those found in liver disease patients 14,15 , these toxic effects may also be transiently induced during exercise, resulting in muscle fatigue.…”
mentioning
confidence: 99%
“…Further, in both clinical observation and mammalian models, there is a direct link between hyperammonemia and increased myostatin expression (Dasarathy, Dodig, Muc, Kalhan, & McCullough, 2004;Kumar et al, 2017;Qiu et al, 2013Qiu et al, , 2012Tsien et al, 2015). Myostatin, a well-known negative regulator of muscle synthesis, plays a pivotal role in degenerative decline in muscle; therefore, the myostatin regulatory pathway is an important target for developing therapies for sarcopenia associated with cirrhosis (Dasarathy, 2012;Dasarathy & Hatzoglou, 2018;Dasarathy et al, 2017;García et al, 2010;Han & Mitch, 2011).…”
Section: Ammonia Toxicitymentioning
confidence: 99%